FROM ALCOHOL TO LITHIASIS - VARIED RISK FACTORS OF CHRONIC PANCREATITIS - Aleksandra Świerczewska; Sylwia Lach; Ilona Bednarek; Kinga Kałuża; Lena Merchel; Karol Seweryn Błąd; Katarzyna Zemsta; Katarzyna Czechowska; Aleksandra Sędek; Olaf Jadanowski (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Chronic pancreatitis is a growing health concern with an incidence of about 10 cases per 100,000 people per year. Alcohol-related CP is more common in men, typically appearing in their 40s or 50s, while idiopathic CP affects both sexes equally. CP is a persistent inflammatory condition of the pancreas, leading to irreversible structural damage, pain, and gradual loss of both exo- and endocrine function. Symptoms include epigastric pain, bloating, digestive issues, glucose intolerance or diabetes, and physical signs like epigastric tenderness, and abdominal mass and jaundice. Materials and methods: A review of 47 sources from publicly available databases such as PubMed and Google Scholar was conducted. Cited publications were published mainly in English. The main topic of these publications was focused on risk factors of CP. State of knowledge: In the following article we discuss the risk factors of CP which are described in acronym TIGAR-O. The main etiology factor of CP is alcohol consumption which is responsible for over a half the cases. Negative effect of ethanol is particularly significant in smokers. Tobacco is an inependent risk factor of CP but combined with alcohol use, risk of chronic pancreatitis is increasing. In the development of pancreatitis gene mutations play a significant role. Autoimmune pancreatitis has two subtypes and its patomechanism is complex. Acute pancreatitis and its recurrences may lead to repetitive inflammation of pancreas and its chronicisation. Obstructive chronic pancreatitis develops due to a mechanical blockage that hinders the flow of pancreatic juice. Conclusions: Expanding access to genetic and immunological testing will help identify groups especially vulnerable to CP, potentially leading to fewer complications, lower treatment costs, and improved treatment outcomes. Understanding how modifiable risk factors affect CP can enhance both primary and secondary prevention efforts.